IMPROVING ABILITY OF STUDENTS IN LISTENING SKILL FOR JUNIOR HIGH SCHOOL BY USING AUDIO-VISUAL METHOD - Mei Sari Hasibuan; Ledy Ana Manalu; Sri Ninta Tarigan (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2022)
Listening skill is the ability to receive and a communication technique where listeners can understand what is heard, so that good communication can be established well too. In this study, the design used by the researcher is the CAR research design (Classroom Action Research) which is carried out with research procedures based on the Kemmis and Taggart principles which include planning, action, observation, reflection or evaluation activities. This study found that the lack of students' ability to listen and listen in learning English makes students' interest in learning decline. To improve students' listening skills in Junior High School, by using audio-visual media as a learning method and how this audio-visual media can influence students to be more active in learning to listen to English well. The data collection of this research was taken from 12 students of SMP DWIWARNA in class VIII, so that this research got a method for good results in the listening learning process using audio-visual for junior high school students. In general, it can be concluded that audio-visual can improve students' focus and concentration in learning listening and the choice of topic material is also very influential on student learning outcomes in listening.